Analisis manajemen modal kerja terhadap profitabilitas pada perusahaan consumer goods yang terdaftar di bursa efek indonesia (2017-2022) - Erric Wijaya; Ossi Ferli; Nur Bunga Natasya; Savira Indah Ariani (Jurnal STEI Ekonomi, 2023)
The COVID-19 pandemic has presented major challenges to various economic sectors, but the consumer goods sector has shown remarkable resilience. This study examines the impact of Working Capital Managementon the profitability of consumer goods companies on the Indonesia Stock Exchange before and during the pandemic. Using panel data from 16 companies, the regression analysis shows that accounts receivable collection period has a negative impact on profitability before the pandemic, while collection period, inventory, and accounts payable are not significant during the pandemic. These results provide insights into Working Capital Managementstrategies that are relevant for consumer goods companies during times of economic crisis, especially in managing critical aspects such as receivables, inventories, and accounts payable. Note: This article serves as a restored version of the original content following a corruption incident. The Digital Object Identifier (DOI) has been successfully re-registered and reactivated to ensure continued accessibility and citation integrity.